KURIKULUM PENDIDIKAN HOLISTIK INTEGRAL (PHI) DALAM PENGUATAN KECAKAPAN SPIRITUAL SISWA SMP ISLAM TERPADU LHI YOGYAKARTA - MARTA JAYA; KARWADI KARWADI (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2022)
Abstract This research aims to analyze the educational curriculum holistically in strengthening students' spiritual abilities. This is done considering the development of the times which makes students' moral dedication very far from perfect. This research uses a qualitative approach using field research. Qualitative research is research that does not use calculations or statistics in its implementation. In this research, the researcher explains that after that it is interpreted according to what is actually in the field, objectively in terms of its implementation at LHI Yogyakarta Integrated Islamic Middle School. Data collection techniques were carried out by means of observation, interviews and documentation which included classroom observations, interviews with the principal, deputy principal for curriculum, teachers and students of the LHI Yogyakarta Integrated Islamic Middle School. Meanwhile, documentation is done by collecting documents that are relevant to this research. The results of this research: The integrative holistic curriculum (PHI) used at the LHI Yogyakarta Integrated Islamic Middle School includes seven literacies, including: Spiritual Skills, Moral Skills, Intellectual Skills, Physical Skills, Interpersonal Skills and Social Skills. Integrative Holistic Education Curriculum (PHI ) in the learning carried out at LHI Yogyakarta Integrated Islamic Middle School is capable and very supportive in strengthening students' spiritual skills because all subjects are integrated with Islamic Religious Education subjects so that students have a lot of time to strengthen students' spiritual skills, this is proven by efforts schools in realizing learning in the process there are Islamic values ​​that are inseparable from all aspects taught